Can Erasmus Exchange Programs help undergraduate tourism students improve their language skills? Mixed methods study with an explanatory sequential design - Okul, Turan; Tanrisevdi, Abdullah (Journal of International Students, 2025)
Erasmus+ supports inter-European exchanges for many students each year. The participants must take a pre- and post-test with Online Language Support (OLS). The study measured students' English development using OLS pre- and post-test scores from 2015 to 2021. Mixed methods with an explanatory-sequential design was utilized in this research. This study demonstrated a notable enhancement in students test scores within the competency levels B1-B2. Integration through joint display analysis helped clarify the quantitative results. Practical and theoretical implications of student exchange programs on language improvement are presented, including length of stay, interaction, and self-confidence.